Preventing and Combating Political Opportunists in Vietnam Today - Tuan, Dr. Nguyen Minh (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Opportunities, political opportunities, opportunism, modern opportunism, etc. are social forces arising from the practice of internal struggle and division within the movement of communism and international workers. It is the inevitable product of the class struggle between the proletariat and the bourgeoisie. Depending on the specific conditions, circumstances, and times of the revolution of each country, the development trend of the era, the nature, level, and manifestation of different types of opportunities are different, but overall is not trivial damage to the proletariat revolution and the cause of building socialism of each country. In Vietnam, according to our perception, the factors of opportunity, political opportunities are not strong enough to become a trend as a trend, but the emergence of political opportunities tends to explode and spreading as fast as it is today, it is imperative to be properly identified and effective deterrent measures are in place. Within the limits of this article, we would only like to approach some aspects of the political opportunity people and the immeasurable consequences of political opportunities in Vietnam today.